Expenditure Inequality in Indonesia, 2008–2010: A Spatial Decomposition Analysis and the Role of Education1. Issue 4 (December 2014) - Hayashi, Mitsuhiro; Kataoka, Mitsuhiko; Akita, Takahiro
<x xml:space="preserve">Abstract</x> Based on the 2008–2010 Susenas panel data, this study examines expenditure inequality from spatial perspectives in Indonesia, using three decomposition methods: (i) a conventional Theil index decomposition; (ii) an alternative Theil index decomposition proposed by Elbers et al. (2008); and (iii) the Blinder−Oaxaca decomposition. Our results show that overall inequality in per capita expenditure increases between 2008 and 2010, which coincides with a rising trend in the official Gini coefficient. The contribution of inequality within urban and rural areas to total inequality is larger than that of inequality between urban and rural areas. Looking within urban and rural areas, urban inequality is significantly higher than rural inequality. Java‐Bali in particular records very high urban inequality. Overall, urban inequality increases, urban–rural inequality remains stable, rural inequality decreases, and inequality at the national level increases. Although urban–rural inequality has a relatively low share in overall inequality, the share is not small enough to ignore its impact. Furthermore, when using the alternative decomposition method, the contribution of urban–rural inequality increases substantially. The present study also found that educational differences appear to have played an important role in expenditure inequality within urban areas and between urban and rural areas.